Effect of the chromaticity of stimuli on night vision disturbances - Castro-Torres, José J.; Casares-López, Miriam; Ortiz-Peregrina, Sonia; Martino, Francesco; Gómez-Robledo, Luis; Jiménez, José R. (Scientific reports, 2024)
The perception of halos and other night vision disturbances is a common complaint in clinical practice. Such visual disturbances must be assessed in order to fully characterize each patient’s visual performance, which is particularly relevant when carrying out a range of daily tasks. Visual problems are usually assessed using achromatic stimuli, yet the stimuli encountered in daily life have very different chromaticities. Hence, it is important to assess the effect of the chromaticity of visual stimuli on night vision disturbances. The aim of this work is to study the influence of the chromaticity of different visual stimuli on night vision disturbances by analyzing straylight and visual discrimination under low-light conditions. For that, we assessed the monocular and binocular visual discrimination of 27 subjects under low illumination using the Halo test. The subjects’ visual discrimination was assessed after exposure to different visual stimuli: achromatic, red, green, and blue, both at the monitor’s maximum luminance and maintaining the same luminance value for the different visual stimuli. Monocular straylight was also measured for an achromatic, red, green, and blue stimuli. The blue stimulus had the greatest effect on halos in both monocular and binocular conditions. Visual discrimination was similar for the red, green, and achromatic stimuli, but worsened at lower luminance. The greatest influence of straylight was observed for the blue stimulus. In addition, visual discrimination correlated with straylight measurements for achromatic stimuli, wherein greater straylight values correlated with an increased perception of halos and other visual disturbances.